Refining the future: A serpentine-based reactive adsorbent for carbon dioxide valorization - Muhammad Faras Heztio; Naelah Aziza Syihab; Caroline Sophia Selena Liem (Journal of Innovation Materials, Energy, and Sustainable Engineering, 2026)
Background: The rising global carbon dioxide CO2 emissions necessitate efficient and sustainable carbon capture solutions, particularly for Indonesia’s industrial sector. This study explores the potential of Aceh serpentinite, a local mineral resource, as a raw material to produce magnesium oxide (MgO) for use as a reactive adsorbent in carbon capture, utilization, and storage (CCUS) technology. Unlike other methods that use expensive imported materials, this research utilizes domestic natural resources through an economical chemical and thermal activation process. Methods: The research methodology involved the preparation of serpentinite samples, which were thermally activated at 700 ℃ for 2 hours to remove hydroxyl groups and enhance mineral reactivity. This was followed by acid leaching using 1M hydrochloric acid (HCl) and precipitation with sodium hydroxide (NaOH) to extract the MgO. Findings: The findings demonstrated that thermal activation led to a mass loss of 9.63% (Loss on Ignition), indicating successful dehydroxylation of the mineral structure. Mass balance calculations estimate that approximately 3.54 grams of MgO could be produced from 13.19 grams of raw rock, representing a process efficiency of 72.8%. Conclusion: The findings confirm that Aceh serpentinite contains sufficient reactive magnesium to be a viable and cost-effective material for CCUS applications, offering a sustainable alternative for industrial emission reduction. Novelty/Originality of this article: The novelty of "REFINE" lies in the strategic use of common local minerals through a simplified and economical chemical path to replace expensive imported carbon capture materials, turning natural resources into high-value environmental products.